Integral sets of one class of breaking dynamic systems - Vyshenskaya , О. V.; Perestyuk , N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The existence of integral sets of a certain class of systems of differential equations, driven by pulses at discrete instants of time, is investigated.